Improvement in fracture strength of porous reaction-bonded silicon carbide with unique surface layer by incorporating α-silicon carbide powder as a secondary phase. Issue 13 (October 2022) - Shimamura, Akihiro; Katsui, Hirokazu; Zhou, You; Hotta, Mikinori; Kondo, Naoki; Fukushima, Manabu
Abstract: This study investigated the effect of incorporating α-phase silicon carbide (α-SiC) powder as a secondary phase on the fracture strength of porous reaction-bonded silicon carbide with a surface layer (porous RB-SiC) mainly based on β-phase SiC (β-SiC). The porous RB-SiC was composed of a highly porous body and surface layer with lower porosity than the porous body. α-SiC powder was incorporated into the porous RB-SiC through powder-based direct foaming followed by reaction sintering. The fracture strength and porous structure of the porous RB-SiC were investigated by varying the amount and particle size of the α-SiC powder. The porous structure composed of β-SiC grain in the porous RB-SiC was strongly influenced by the incorporation of α-SiC powder. Fracture strength of porous RB-SiC increased from 27.1 ± 1.4 MPa (without α-SiC powder) to 39.9 ± 2.0 MPa as maximum by incorporation of α-SiC, resulting in fracture strength improvement by up to 1.5 times.